"Głupstwo i rozmaite jego odcienie" - leksykalno-stylistyczne wyznaczniki głupoty na przykładzie "Charakterów rozumów ludzkich" Michała Wiszniewskiego = "Głupstwo i rozmaite jego odcienie" ("Footling and its Various hades") - lexical and stylistic indicators of stupidity on the basis of "Charaktery rozmów ludzkich" ("The characters of human talks") by Michał Wiszniewski - Seniów, Adrianna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of this article is to analyse lexical and stylistic indicators of stupidity that can be found in one of the chapters of Wiszniewski`s novel entitled "Głupstwo i rozmaite jego odcienie" ("Footling and Its Various Hades"), in which the author named and discussed as many as sixteen types of different mental deficiencies as well as he listed the symptoms typical for each one of these.
Keywords: stylistyka; historia języka; słownictwo psychologiczne; stylistics; history of language; psychological vocabulary